Arge davidsmithi nom. nov. for Arge davidi Shinohara & Hara, 2017 (nec Koch & Liston, 2012) (Hymenoptera, Argidae) - Shinohara, Akihiko; Hara, Hideho (Zootaxa, 2018)
Koch & Liston (2012) described an argid sawfly from South Africa and named it Arge davidi Koch & Liston, 2012. Shinohara & Hara (2017) very recently described another argid from Taiwan under the same name, Arge davidi Shinohara & Hara, 2017. The latter authors simply overlooked Koch & Liston’s (2012) taxon and Arge davidi Shinohara & Hara, 2017, is a primary junior homonym of Arge davidi Koch & Liston, 2012.